2021
DOI: 10.1021/acs.jpcb.1c02180
|View full text |Cite
|
Sign up to set email alerts
|

Structure-Redox Response Correlation in a Few Select Heme Systems Using X-ray Absorption Spectroelectrochemistry

Abstract: Heme based biomolecules control some of the most crucial life processes, such as oxygen and electron transport during respiration and energy metabolism, respectively. The active site of the heme, viz., the metal center, plays a key role and attributes functionality to these biomolecules. During the oxygen binding and debinding processes, it is important to note that the oxidation state of iron in hemoglobin (+II in the native form) does not undergo any change. However, the spin states of the metal center chang… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…In another study, Bhattacharyya et al , 76 reported operando XAS of heme-based biomolecules. They performed Fe K-edge XAS studies in homogenous conditions under electrochemical control simultaneously measuring cyclic voltammetry.…”
Section: Introductionmentioning
confidence: 99%
“…In another study, Bhattacharyya et al , 76 reported operando XAS of heme-based biomolecules. They performed Fe K-edge XAS studies in homogenous conditions under electrochemical control simultaneously measuring cyclic voltammetry.…”
Section: Introductionmentioning
confidence: 99%
“…Hemoglobin (Hb) and myoglobin (Mb) are the main color-forming proteins in animal meat. Hb is mainly found in blood and is responsible for carrying oxygen and participating in redox reactions in living organisms (Samajdar and Bhattacharyya 2021). Hb is composed of four subunits, each of which is composed of peptide chains and heme molecules, and Hb is oxidized to methylated hemoglobin during the processing and storage of meat.…”
Section: Introductionmentioning
confidence: 99%